13.5k views
1 vote
Find the second, fourth, and eleventh terms of the sequence A(n) = 5 + (n - 1)(-3)​

User Big Rich
by
4.4k points

1 Answer

2 votes

Answer:

2nd: 2

4th: -4

11th: -25

Explanation:

When you substitute a number into the equation you get that number term. So, if you substituted in 1, you get the first term. To find the second term, you substitute in 2:

A(2) = 5 + (2 - 1)(-3)

A(2) = 5 + (1)(-3)

A(2) = 5 - 3

A(2) = 2

To get the 4th term you substitute in 4:

A(4) = 5 + (4 - 1)(-3)

A(4) = 5 + (3)(-3)

A(4) = 5 - 9

A(4) = -4

And we do the same for the 11th term:

A(11) = 5 + (11 - 1)(-3)

A(11) = 5 + (10)(-3)

A(11) = 5 - 30

A(11) = -25

User JoshuaBoshi
by
5.2k points